Impacts of Displacement on Urban Livelihoods : A Railway Project in Metro Manila - Choi, Narae (Taylor and Francis, 2015)
This article seeks to understand the ways in which urban livelihoods are affected by development-induced displacement, with a particular focus on residents remaining in the locality. Through an empirical case study of a railway upgrading project in Metro Manila, the article investigates livelihood impacts of large-scale demolition and displacement, which varied depending on whether the physical capital of remaining residents declined due to land clearance and the extent to which they relied on the local livelihood network established with displaced settlers. In comparison, households remained intact when they had little engagement with the local informal economy.